Politizacija kulturnega polja na Slovenskem v obdobju prve Jugoslavije - Mithans, Gašper (Poligrafi, 2020)
The article addresses the issue of the politicization of literature and filmography in the Slovenian part of the Kingdom of SHS/Yugoslavia, focusing on the analysis of cultural journals and disputes over the autonomy of authors and editors. The-se conflicts in the 1930s, following almost the same pattern, led to divisions and major disagreements between and in all three major political camps: Catholic, liberal, and Marxist. A striking example of internal conflict would be the dissent between the Catholic Right and the Catholic left precisely in the cultural field with the publication of Edvard Kocbek%s treatise on the Spanish Civil War in the journal Dom in svet. The general public became involved in the heated debate. filmography, although underrated by most cultural figures, was used in Slove-nia % albeit with a considerable lag compared to other European nations % befo-re, during, and after World War II as a propaganda tool of the agents of political Catholicism and the Marxists (including the liberation front) alike.
Keywords: artistic autonomy; avtorska svoboda; cultural field; filmografija; filmography; katoliški tabor; Kingdom of Yugoslavia; književnost; Kraljevina Jugoslavija; kulturno polje; literature; marksisti; Marxists; political catholicizm